Incontinence and psychological symptoms in Phelan‐McDermid syndrome. Issue 1 (29th October 2019) - Hussong, Justine; Wagner, Catharina; Curfs, Leopold; von Gontard, Alexander
Abstract: Aims: Phelan‐McDermid syndrome (PMD) is a congenital syndrome caused by a deletion on chromosome 22q13.3. About 600 cases have been identified worldwide. PMD is characterized by neonatal hypotonia, moderate/severe intellectual impairment, impaired expressive language, and typical dysmorphic features. Psychological symptoms as hyperactivity, attention problems, restlessness, and stereotyped‐repetitive behavior were reported. The aim of the study was to assess incontinence and associated psychological problems in PMD. Methods: Forty‐one individuals with PMD were recruited through a German support group (48.8% male; mean age 13.4 years; range, 4‐55 years). Parents or caregivers completed the developmental behavior checklist (DBC), as well as the parental questionnaire: enuresis/urinary incontinence, including six questions on adaptive toileting skills. Results: Rates of nocturnal enuresis (NE), daytime urinary incontinence, and fecal incontinence were 86%, 73%, and 79%. Rates were similar in all age groups (children, teens, adults). Constipation was present in 19%. Forty‐two percent of the sample had a clinically relevant DBC score, with adults more affected than teens. Persons with NE had significantly higher "anxiety/depression" subscale scores. Toileting skills were more developed in adults than in children. Sixty‐eight percent had further physical disabilities. Conclusions: Incontinence rates in PMD are high in all age groups. However, persons with PMD can improve their toilet skills. Therefore, the assessment and treatment of incontinence in persons with PMD is recommended. Constipation does not seem to be a major problem in PMD. Due to the high prevalence rates of somatic conditions, an assessment for organic and functional incontinence is recommended.